Wonder and Moral Education. Issue 1 (27th June 2018) - Schinkel, Anders
ABSTRACT: Many authors have claimed a moral and educational significance for wonder. In this article Anders Schinkel assesses these claims in order to address the question whether we do indeed have reason to stimulate the sense of wonder and to provoke experiences of wonder in education with a view to its moral effects or importance. Are there moral effects of wonder — or does wonder have a moral significance — that give us a (further) reason to promote children's sense of wonder and to attempt to elicit the experience of wonder in children? And if so, will any experience of wonder do, from a moral perspective, or do only some experiences of wonder — in specific contexts, or with a specific object — have the desired effect? Schinkel argues that, although there is certainly a case to be made for wonder's moral (educational) importance, it needs to be made cautiously. Wonder coheres more easily with some emotions and attitudes than with others, but in the end its moral significance depends to a large extent on how we interpret or make sense of our wonder and what we wonder at. In moral education, therefore, the value of wonder depends on how it is framed and morally charged.